Thomas Jefferson papers - Jefferson, Thomas, 1743-1826.
Chiefly correspondence.
Microfilm of originals in the American Philosophical Society, Philadelphia, Pa.
American Philosophical Society
U.S. president, vice president, and secretary of state; diplomat, architect, inventor, planter, and philosopher.
Individually cataloged in the manuscript catalog of the American Philosophical Society.
Keywords: Cabinet officers; Diplomats; Plantation owners; Presidents -- United States; Vice-Presidents -- United States